The Influence of Islamic Philanthropy, Macroeconomics, Socio-Demography, on Poverty in Muslim Minority Provinces in Indonesia (2019-2023) - Wahdatul Nadia Rawi; Putra, Trischa Relanda (Universitas Muhammadiyah Pontianak, 2026)
Poverty in Indonesia's Muslim-minority provinces remains a multidimensional issue influenced by economic, social, and welfare distribution factors. This study aims to analyze the effects of Islamic philanthropy, macroeconomic conditions, and socio-demographic factors on poverty during 2019–2023. Using panel data regression with secondary data from BPS, BAZNAS, and related institutions, the results show that infaq and sadaqah, population size, and the Human Development Index significantly affect poverty, while zakat, DSKL, GRDP, APBD, social assistance, education, economic growth, minimum wage, inflation, and unemployment do not. These findings highlight the importance of human development and community-based Islamic philanthropy in poverty reduction policies.